The risk factors of failed reimplantation arthroplasty for periprosthetic hip infection - Jhan, Shun-Wun (BMC Musculoskelet Disord, 2017)
BACKGROUND: Two-stage reimplantation arthroplasty is one of the standard treatments for chronic periprosthetic joint infection (PJI). Scanty data exist regarding the risk factors for failure after two-stage reimplantation for periprosthetic hip infection. The purpose of this study was to investigate and identify the risk factors associated with failure after two-stage reimplantation hip arthroplasty. METHODS: Sixty-two patients with hip PJI treated with a two-stage reimplantation protocol at our institution from 2005 to 2012 were reviewed. Patients requiring medical treatment or reoperation for recurrent infection were defined as treatment failure. A multivariate Cox proportional hazards model was used to analyze the risk factors associated with treatment failure. RESULTS: Of the 62 patients, 11 (17.7%) patients had developed reinfection after the two-stage reimplantation with a mean follow-up of 5.7 years. The implant survival was 82.2% (95% confidence interval [CI] 75.19−92.55) at 10 years. Multivariate analysis revealed BMI ≥30 kg/m(2) (hazard ratio [HR] 9.16; 95% CI 1.51−55.3; p = 0.0158), liver cirrhosis (HR 6.39; 95% CI 1.09−37.4; p = 0.0398), gram-negative organism (HR 5.68; 95% CI 1.18−27.4; p = 0.0303), and presence of sinus tract (HR 18.2; 95% CI 2.15−153; p = 0.0077) as the independent risk factors for treatment failure. CONCLUSIONS: We found obesity, liver cirrhosis, gram-negative organism, and the presence of sinus tract were significantly related to the risks of failure after reimplantation arthroplasties.